2018
DOI: 10.1016/j.scienta.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postharvest UV-C treatment on the microbial quality of ‘Şalak’ apricot

Abstract: Inactivation of natural flora found on cv. 'Şalak' apricot surfaces was investigated using a newly designed UV-C treatment system equipped with four UV lamps and a rotating roller bearing. Multiple Point Source Summation (MPSS) Model was used to estimate UV light intensity field in this processing chamber. Although MPSS model over-predicted the UV intensity data, light intensity profile showed a good agreement with the radiometric measurements. UV-C treatment of apricots resulted in 3-log reduction in the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The UV-C wavelength of 254 nm has the most effective germicidal effect. Numerous studies have reported effective UV-C inactivation of microorganisms, when applied to fresh or fresh-cut fruits and vegetables [178][179][180]. UV-C may also positively affect the storage of fresh and fresh-cut fruits and vegetables by reducing oxidative or cell wall-degrading enzyme activities [181,182].…”
Section: Uv-c Radiation and Its Effect On Fcpmentioning
confidence: 99%
“…The UV-C wavelength of 254 nm has the most effective germicidal effect. Numerous studies have reported effective UV-C inactivation of microorganisms, when applied to fresh or fresh-cut fruits and vegetables [178][179][180]. UV-C may also positively affect the storage of fresh and fresh-cut fruits and vegetables by reducing oxidative or cell wall-degrading enzyme activities [181,182].…”
Section: Uv-c Radiation and Its Effect On Fcpmentioning
confidence: 99%
“…Such a reduction was attributed to the contribution of the UV-C on the disruption of the cell membrane integrity of microbes, damaging nucleic acids and inducing mutation, thereby retarding microbial growth [32]. However, at a higher UV-C dose, longer exposure time and longer storage time, the microorganisms might show different responses due to self-adjustment or adaptation of the microorganisms to the applied UV-C dose; the aggregation of microbial cells can form shields and prevent direct exposure to UV-C, developing resistance to the UV-C [35].…”
Section: Effect Of Storage Conditions and Uv-c Treatment On Microbial...mentioning
confidence: 99%
“…were achieved in fresh cut broccoli and green tomato after exposure to 0.0015 J cm À2 and 0.178 J cm À2 UV dose, respectively (Lim and Harrison, 2016;Martinez-Hernandez et al, 2015). On the other hand, less than 3 log reductions were recorded in apricot (3.1 J cm À2 ), watermelon (0.72 J cm À2 ), apple (2.4 J cm À2 ) and pear (0.17 J cm À2 ) samples after UV treatment at different UV dose levels (Hakguder and Unluturk, 2018;Syamaladevi et al, 2014;Manzocco et al, 2011;Artés-Hernández et al, 2010). Furthermore, higher than 1 log inactivation of hepatitis A virus (HAV) murine norovirus (MNV) was reported in UV treated blueberries (1331 mJ cm À2 ) (Butot et al, 2018).…”
Section: Microbial Quality Of Liquid Foods Treated With Uv Lightmentioning
confidence: 99%